Japan’s Contribution to Bangladesh’s Human Resource Development (Journal of the Asiatic Society of Bangladesh, Humanities, 2025)
Japan has been a time-tested partner of Bangladesh in terms of its human resource development, as well as many other development areas. Bangladesh's demographic dividend offers immense future possibilities, but improper utilisation could lead to demographic disaster and hinder progress in various sectors. Taking all these into account, this qualitative study evaluates the initiatives taken by Japan for human resource development in Bangladesh. The major findings of the study portray that Japan has been cooperating with Bangladesh in higher education through several scholarship programmes, providing work opportunities to young Bangladeshi citizens in several mega projects in Bangladesh (e.g., the Matarbari project, the MRT project), and so on. However, there are some issues in Bangladesh, such as a lack of proper measures to establish industry-academia relationships and a lack of proper utilisation of the TVET programmes, as well as some considerable differences between Bangladeshi people’s and Japanese people’s mindsets due to different cultural and moral backgrounds. If these obstacles are effectively dealt with, great opportunities lie ahead for Bangladesh. On the basis of these findings, this study recommends that Bangladesh should take effective measures to benefit from Japan’s relaxed visa policies; drastic changes need to be introduced in Bangladesh’s work culture; and effective measures should be taken to remove all the obstacles facing Japanese human resource initiatives.JASBH, Vol. 70(1), June 2025, pp. 37-64